Glycemia and Atherosclerotic Cardiovascular Disease: Exploring the Gap Between Risk Marker and Risk Factor - Nahmias, Avital; Stahel, Priska; Xiao, Changting; Lewis, Gary F. (Frontiers in Cardiovascular Medicine, 2020)
There is consistent, unequivocal and reproducible epidemiological evidence derived from diverse populations that various indices of glycemia (fasting plasma glucose, postprandial or post oral glucose challenge plasma glucose, HbA1c) are associated with an increased risk of atherosclerotic cardiovascular disease (ASCVD), even in the prediabetic state. Furthermore, there is abundant experimental evidence demonstrating that hyperglycemia per se accelerates and aggravates the atherosclerotic process, providing biological plausibility to the concept that hyperglycemia is causally related or a true risk factor for ASCVD. Two studies in particular, DCCT and UKPDS, that enrolled a younger cohort of patients with type 1 diabetes or an older cohort with newly diagnosed type 2 diabetes, respectively, showed trends towards a reduction in ASCVD. The reductions in ASCVD reached statistical significance only after prolonged follow up, and when differences in HbA1c were no longer maintained (referred to by some as a ‘legacy effect’). More recent studies in those with established type 2 diabetes, in which glycemic control was improved by a variety of strategies, failed to demonstrate reductions in ASCVD. The gap in evidence supporting hyperglycemia as a true causative risk factor for ASCVD or simply a risk marker for some other confounding causative factor is discussed in this review. We conclude that hyperglycemia does appear to be at least partially causative of ASCVD (ie. an ASCVD risk factor). We discuss how this evidence can be incorporated into an overall therapeutic strategy to prevent ASCVD in those with prediabetes and established diabetes.